2013
DOI: 10.5301/jn.5000264
|View full text |Cite
|
Sign up to set email alerts
|

Vascular access in older patients: 
an Italian survey

Abstract: A fistula is the gold standard for hemodialysis vascular access in older patients if judged appropriately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…A knowledge of the different surgical techniques [53] is helpful in making the nephrologist a more active proponent of AVF creation. As demonstrated in a recent Italian survey, AVF still remains the dialysis access with highest prevalence also in older patients, with an excellent survival rate [55]. Again, the Italian data from the DOPPS study confirm the high rate of AVFs both in the prevalent and, more importantly, in incident patients [56].…”
Section: An Italian Perspectivementioning
confidence: 74%
“…A knowledge of the different surgical techniques [53] is helpful in making the nephrologist a more active proponent of AVF creation. As demonstrated in a recent Italian survey, AVF still remains the dialysis access with highest prevalence also in older patients, with an excellent survival rate [55]. Again, the Italian data from the DOPPS study confirm the high rate of AVFs both in the prevalent and, more importantly, in incident patients [56].…”
Section: An Italian Perspectivementioning
confidence: 74%
“…This contrasts with an Italian survey where CVC significantly affects mortality. 9 Age was the only statistically significant factor associated with death (p=0.045) which is comparable to the Italian population (p<0.001). 9 In contrast, the mortality benefit of AVF is consistently superior to that of AVG and CVC for patients of all ages.…”
Section: Discussionmentioning
confidence: 58%
“…7 A recent survey on the Italian population showed no difference in fistula outcome in old age with primary patency of 73 %, 8 contrary to Richardson et al, reported, who reported primary patency of 35 % at one year. 9 The currently available literature concludes that every centre has variable outcomes and optimum hemodialysis access for the elderly population is yet to be defined. 10 Therefore, the present study aimed to determine the outcome of arteriovenous-fistula in our elderly population as per the latest KDOQI guidelines and compares it with younger age groups so that the best approach to hemodialysis access can be defined.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of patients who are using a native arteriovenous fistula as a vascular access varies remarkably between Europe and the United States (US). It is interesting to note, that the use of AV fistulas is much more common in Europe than in the US, while patients on hemodialysis have lower comorbidity in Europe than in the US as it was shown in the DOPPS study [12]. More than half of the US dialysis patients receive a synthetic arteriovenous graft.…”
Section: Arteriovenous Fistulasmentioning
confidence: 89%